Advancing Library Services for Mobile Users - Liu, Yan Quan (IGI Global Scientific Publishing, 2025)
As mobile technology becomes integral to everyday life, libraries rework their services to meet the needs of their users. Advancing library services for mobile users requires seamless, intuitive experiences that support research, learning, and engagement. From mobile-friendly catalogs and e-book pla...
Publication Title: https://services.igi-global.com/resolvedoi/resolve.aspx?doi=10.4018/978-1-7998-9175-8
Keywords: dept.ils

Services to mobile users: the best practice from the top-visited public libraries in the US - Liu, Yan Quan; Lewis, Sarah (Information Technology and Libraries, 2023)
Libraries are adapting to the changing times by providing mobile services. One hundred fifty-one libraries were chosen based on circulation, with at least one library or library system from each state, to explore the diverse services provided to mobile users across the United States. According to the data, mobile apps, mobile reference services, mobile library catalogs, and mobile printing are among public libraries’ most-frequently offered services, as determined by mobile visits, content analysis, and librarian survey responses. Every library examined had at least one mobile website, mobile catalog, mobile app, or webpage adapted for a mobile device. Following the COVID-19 outbreak, services such as mobile renewal, subscriber database access, mobile reservations, and the ability to interact with a librarian were expanded to allow better communication with customers—all from the comfort and safety of their own homes. Libraries are continually looking for innovative methods to assist their mobile customers as the world changes.
0 citations (Crossref) [2023-10-31] Number: 1
Keywords: Mobile Apps; Mobile services; Public Libraries; SCSU-student; Survey study; dept.ils; peer-reviewed

Public library events: Who, what, where, when, and why? - Kukiolczynski, Katie Teresa; Liu, Yan Quan (Public Library Quarterly, 2021)
An explorative survey pertaining to organization and execution of programs and events offered in public libraries across Connecticut revealed that library programs have been steadily increasing in recent years, with most libraries providing one hundred or more programs a year. The types of programs that are most popular vary throughout the library’s open hours. Children’s programming appears to be more popular during the day while adult programming is more popular in the evening. Program popularity is based on grouping and continuous support from external partners. While this study confirmed that both library space and library staff sizes are adequate for programming, a further investigation would assert that this is the case within nationwide library programming.
1 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85103569958
Keywords: Connecticut; Public libraries; dept.ils; library events; library programs; peer-reviewed

Adopting Critical Cataloging Practices Post Diversity Audit: Connecting the Community to Your Collection - Anderson, Jessica K.; Liu, Yan Quan (Library Resources & Technical Services, 2025)
To increase patrons’ ability to find resources, it is imperative to investigate barriers and biases in thedescriptive catalog data for inclusive collection management and development standards. This studyused a specially designed descriptive approach to gather quantitative data from 101 public librariansin Connecticut via a Qualtrics survey to identify the key variables that influence the successfulenhancement of online public access catalog (OPAC) metadata after a diversity audit of the librarymaterials. The results revealed factors that promote or impede the integration of inclusive catalogingthat reflects the diversity of the community: (1) appreciating the benefits of audit methods that arefocused on bibliographic records, (2) recognizing the need for buy-in and participation from theentire organization, and (3) stressing the useful integration of institutional and community feedbackto improve the collection’s accessibility and representation. The findings provide practical adviceto public libraries that want to satisfy the diverse demands of their user base by integrating criticalcataloging frameworks into their diversity and inclusion objectives.
Keywords: SCSU-student; dept.ils

Private post-secondary library websites and the ADA: compliancy and COVID-19 - Bielefield, Arlene; Liu, Yan Quan; Waimon, Victoria (Universal Access in the Information Society, 2023)
This study explores whether US post-secondary institutions (PPI) follow philosophies to foster inclusive communities, providing resources for those individuals with disabilities thrive socially, personally, and academically, while there have been no thorough studies conducted to determine web accessibility of the nation’s top-ranked PPI library webpages. Additionally, this study pioneers in comparison with the accessibility of PPI’s library homepages fighting COVID-19. The study evaluated the library homepages of the premium PPIs based on Money.com’s 2019 list of “The Best Colleges in America” via the WAVE web accessibility evaluation tool. The outcomes determined that most of the library homepages analyzed were littered with numerous errors, and the shift to online-based research in learning had no significant impact on the number of errors WAVE detected. The disconcerting findings of this study demonstrate the overall failure to recognize the importance of web accessibility or perhaps even the indifference toward accessibility on the part of the PPI community.
Keywords: ADA; Academic libraries; Accessibility; COVID-19; Disability; Overall failure; Philosophical aspects; Post-secondary institutions; Private colleges and universities; SCSU-student; Section 508; WAVE; WCAG; Web accessibility; Websites; dept.ils; peer-reviewed

Exploring library core competencies: A text mining study of american library association’s job advertisements from 2006 through 2017: - Yang, Qinghong; Shi, Zehong; Liu, Yan Quan (Social Science Computer Review, 2021)
Are core competency requirements for relevant positions in the library shifting? Applying natural language processing techniques to understand the current market demand for core competencies, this study explores job advertisements issued by the American Library Association (ALA) from 2006 to 2017. Research reveals that the job demand continues to rise at a rate of 13% (2006–2017) and that the requirements for work experience are substantially extended, diversity of job titles becomes prevalent, and rich service experience and continuous lifelong learning skills are becoming more and more predominant for librarians. This analytical investigation informs the emerging demands in the American job market debriefing the prioritization and reprioritization of the current core competency requirements for ALA librarians. © The Author(s) 2021.
0 citations (Crossref) [2023-10-31]
Keywords: dept.ils; peer-reviewed

Academic pursuits and involvement in decision-making: study on the formation of U.S. university think tanks - Lyu, Qing; Bielefield, Arlene; Liu, Yan Quan (Administrative Sciences, 2023)
This paper analyzes the concept of think tanks and concludes that think tanks have three basic characteristics. Firstly, they are based on academic research, relatively independent operation, and aim to serve scientific decision-making. Taking Ivy League think tanks as an example, this paper provides a preliminary discussion of ways for think tanks to maintain the scientific nature of their research, maintain the independence of their operations, and disseminate research results to enhance their influence. It covers institutional mission, research team construction, institutional governance, fundraising, achievements and activities, and alumni networks. This paper proposes a framework of university think tank generation paths associated with the essential characteristics of think tanks. The paper points out that, as a research consulting organization grown out of universities, university think tanks must maintain the scientific nature and independence of research while providing support and services for decision-making. Only in this way can they truly serve scientific and democratic decision-making, gain the trust of the public and have a real lasting influence.
0 citations (Crossref) [2023-10-31] Number: 3
Keywords: American university affiliated think tank; characteristics of think tank; decision-making; dept.ils; peer-reviewed; the ivy league university; think tank operation mechanism

ADA digital accessibility on academic library websites - Liu, Yan Quan; Bielefield, Arlene; Beckwith, Jennifer (College & Research Libraries, 2024)
Studying ADA accessibility at library websites of top universities selected from the U.S. News and World Report, the authors used WAVE and AChecker to assess data in compliance with WCAG 2.0 standards. Almost 8 out of 10 public university academic libraries reported accessibility errors as one of the major findings. Low color contrast was becoming a more commonly occurring accessibility issue, making it difficult for people with vision impairments to perceive the color of the image. The outcomes of the study suggest that academic libraries around the world should continue improving their website accessibility.
Keywords: SCSU-student; dept.ils; peer-reviewed

The provision of patron services in Chinese academic libraries responding to the COVID-19 pandemic - Guo, Yajun; Yang, Zinan; Yang, Zhishun; Liu, Yan Quan; Bielefield, Arlene; Tharp, Gregory (Library Hi Tech, 2020)
Purpose: The purpose of this paper is to identify the measures employed in the provision of patron services in Chinese academic libraries responding to the COVID-19 pandemic, noting the challenges and issues inherent in providing substantial services while undergoing a public health emergency. Design/methodology/approach: This paper uses an analytical survey study of 137 Chinese academic libraries using data collected through a combination of website investigation, social media access and direct correspondences. Findings: Over 94% of Chinese academic libraries released COVID-19-related information through their websites; the majority switched their service focus to partly or solely remotely online, including remote access, free electronic resources, virtual references reachable 24/7 and research support services deliverable online; services of print materials were altered to e-books for conveniences. Research limitations/implications: It should be noted that the survey was conducted from February 12 to April 5, 2020; because of the rapid updates to the library's website and social media channels, the status of their patron services are in the process of dynamic changes and that there should be many libraries that have adopted some patron service methods, but this study is difficult to cover comprehensively. In addition, patron services carried out offline by the surveyed libraries but not disclosed on the online platform could not be analyzed in a way that would be consistent with the data provided by the survey. Originality/value: By providing evidence of the current status of patron services in Chinese academic libraries during the COVID-19 pandemic, this study helps fulfill the scant empirical attention given to the impact of nationwide public health crises on academic libraries and offers new data of the best practices that help library administrators enhance the impact, efficiency and value of library services to their target community users. © 2020, Emerald Publishing Limited.
32 citations (Crossref) [2023-10-31] tex.ids: guoProvisionPatronServices2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85088570958 type: Article
Keywords: Academic libraries; COVID-19; China; Patron services; Survey; Virtual services; dept.ils; peer-reviewed